The Pregnancy Recovery Center: A women-centered treatment program for pregnant and postpartum women with opioid use disorder. (November 2018) - Krans, Elizabeth E.; Bobby, Stephanie; England, Michael; Gedekoh, Robert H.; Chang, Judy C.; Maguire, Bawn; Genday, Patty; English, Dennis H.
Abstract: Objective: To evaluate the impact of women-centered substance abuse treatment programming on outcomes among pregnant women with opioid use disorder (OUD). Methods: We compared two retrospective cohorts of pregnant women with OUD on buprenorphine maintenance therapy who delivered an infant at the University of Pittsburgh from 2014 to 2016. Cohort 1 was composed of pregnant women who received women-centered OUD treatment services through the Pregnancy Recovery Program (PRC) and Cohort 2 was composed of pregnant women who received buprenorphine at OUD programs without women-centered services (non-PRC). Women-centered outcomes were defined as a) pregnancy-specific buprenorphine dosing, b) prenatal and postpartum care attendance, c) breastfeeding and d) highly effective contraception utilization. Chi-square and t -tests were used to compare outcomes between PRC and non-PRC patients. Results: Among 248 pregnant women with OUD, 71 (28.6%) were PRC and 177 (71.4%) were non-PRC patients. PRC patients were significantly more likely to initiate buprenorphine during vs. prior to their pregnancy (81.4% vs. 44.2%; p  < .01) and have a higher buprenorphine dose at the time of delivery (16.0 mg vs. 14.1 mg; p  = .02) compared to non-PRC patients. Likewise, PRC patients were significantly more likely to attend their postpartum visit (67.9% vs. 52.6%; p  = .05) and receive a long-acting reversible contraceptive (LARC) method (23.9% vs. 13.0%, p  = .03) after delivery compared to non-PRC patients. Finally, PRC patients had a smaller percent decrease in the rate of breastfeeding during their delivery hospitalization (−14.7% vs. −37.1%). Conclusions: Incorporating women-centered services into OUD treatment programming may improve gender-specific outcomes among women with OUD. Highlights: Pregnant and postpartum women with opioid use disorder have unique treatment needs. Providing women-centered treatment services may improve gender-specific outcomes. Women-centered services may decrease barriers to treatment engagement in pregnancy.